COMMUNITY RAINWATER HARVESTING FINANCIAL PAYBACK ANALYSES - CASE STUDY in MALAYSIA - Bee Woon Y.; Ling L.; Lun Tan W.; Fai Chow M. (Institute of Physics Publishing, 2023)
Catchments; Floods; Harvesting; Investments; Runoff; Urban growth; Water conservation; Water supply; Annual maintenance; Annual rainfall; Fresh water resources; Rain water harvesting; Runoff reduction; Underground storage tanks; Urban development; Water shortages; Rain